PENGARUH INTERAKSI EDUKATIF TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI KELAS V SDN 015 JAKE KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Hazman Hazman; Sopiatun Nahwiyah; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2023)
The learning process always requires students to achieve learning objectives well. Efforts are always made to achieve this goal is to conduct educational interactions. Ideally, if the educative interaction is carried out well, it will affect student learning motivation. However, for the fifth grade students of SDN 015 Jake, the opposite happened. Student learning motivation is still low. Based on the background and phenomena above, this study aims to determine whether there is an effect of educative interaction on students' learning motivation in the subjects of Islamic Religious Education and Morals for class V SDN 015 Jake, Kuantan Tengah District, Kuantan Singingi Regency. This research is a causal associative quantitative research, which was conducted at SDN 015 Jake, Kuantan Tengah District, Kuantan Singingi Regency. The primary data collection technique used is a questionnaire. Meanwhile, to collect secondary data, researchers used interview, observation and documentation techniques. Data analysis used a simple linear regression formula which was then processed using SPSS 20.0 software. The results of this study indicate that the significance value (Sig.) of 0.023 is smaller than the probability of 0.05. It can also be seen from the t-count value of 2.354 which is greater than the t-table value of 2.021. And it can be seen from the value of the Coefficient of Determination (R Squere) of 0.117 or if it is a percentage the magnitude of the influence of variable X on variable Y is 11.7%. So it can be concluded that there is an effect of educative interaction on students' learning motivation in the subjects of Islamic Religious Education and Morals for class V SDN 015 Jake, Kuantan Tengah District, Kuantan Singingi Regency.